1993
DOI: 10.1002/lsm.1900130602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 830 nm continuous wave laser diode irradiation on median nerve function in normal subjects

Abstract: The presence, magnitude, and nature of the effect that low intensity laser irradiation has on nerve function, growth, and repair constitute a contentious area of research. We have addressed one aspect of this controversy by systematically examining the influence of 830 nm laser radiation on median nerve function. In particular, we investigated median nerve motor and sensory distal latencies, action potential amplitudes, action potential areas, and conduction velocities as well as dorsal hand skin temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 23 publications
(2 reference statements)
0
25
0
2
Order By: Relevance
“…These latter studies have indicated significant laser-mediated increases in median nerve conduction latencies compared with placebo and that such effects are apparently dose dependent [14] and localised to the site (and ipsilateral side) of irradiation [13]. Furthermore, application of higher radiant exposures with this same model (1.2 J per point; ∼12 J/cm 2 ) has been found by Basford's group to decrease nerve conduction latencies [16]. In contrast to these generally positive findings, assessment of the potential relevance of pulsing by using a modulated output source (820 nm; 40 mW average output) found no significant laser-mediated effects when compared with sham controls [15].…”
Section: Introductionmentioning
confidence: 84%
“…These latter studies have indicated significant laser-mediated increases in median nerve conduction latencies compared with placebo and that such effects are apparently dose dependent [14] and localised to the site (and ipsilateral side) of irradiation [13]. Furthermore, application of higher radiant exposures with this same model (1.2 J per point; ∼12 J/cm 2 ) has been found by Basford's group to decrease nerve conduction latencies [16]. In contrast to these generally positive findings, assessment of the potential relevance of pulsing by using a modulated output source (820 nm; 40 mW average output) found no significant laser-mediated effects when compared with sham controls [15].…”
Section: Introductionmentioning
confidence: 84%
“…[26][27][28] Most reports on the effect of LLLT on PNS injury are in cases of axonotmesis. [13][14][15][18][19][20][21]25,[29][30][31][32] However, promising results have been obtained in severe cases of neurotmesis when LLLT is used in combination with or Gore-Tex tubes. 27 The cutaneous branch consisted of 400 myelinated and 1800 unmyelinated afferent axons.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, uma possível explicação seria que a irradiação do laser (3 J) inibiu as fibras nervosas aferentes de grande diâmetro, promovendo enfraquecimento do sistema inibitório espinhal 33 . Outra hipótese seria que o laser teria alterado a condução nervosa periférica 21 , porém com este estudo essa hipótese não pôde ser confirmada devido a não mensuração dessa variável.…”
Section: Dados Do Limiar De Dor Por Pressãounclassified
“…O LBP vem sendo usado com o objetivo de promover efeitos analgésicos [4][5][6][7] , modulação da inflamação [8][9][10][11][12][13][14] , efeitos cicatriciais [15][16][17] e vasodilatadores locais 19 , sem os riscos de produção de calor e dano ao tecido irradiado 7,18,19 . A ação analgésica da laserterapia pode ser explicada a partir de algumas hipóteses: modulação dos processos inflamató-rios 3,9,20 , alteração da excitação e condução nervosa dos neurônios periféricos 21,22 , liberação de opioides endógenos 23,24 e aumento na síntese de serotonina 4,25 . Acredita-se também que o LBP pode gerar um efeito sistêmico pelas mudanças metabólicas tanto no local da irradiação como em áreas mais distantes devido ao fato de substâncias serem liberadas na circulação sanguínea 26,27 , como também ocorrer vasodilatação e aumento do fluxo sanguíneo [28][29][30][31] .…”
Section: Introductionunclassified